Testing Lecture Comprehension Through Listening-to-summarize Cloze Tasks The Trio of Task Demands, Cognitive Processes and Language Competence - Wang, Haiping (Springer Singapore, 2018)
This book explores the effectiveness of listen-to-summarize tasks as a tool to assess lecture comprehension ability. It especially focuses on listen-to-summarize tasks that represent listeners' meaning building and the discourse construction of the lecture for listening assessment purposes. It discusses in depth the nature of lecture comprehension and introduces the approaches to assessing it. It also presents teachers' and students' perceptions of listen-to-summarize task demands and their respective implications. By observing interactions between test-takers' cognitive processes and the task itself, the book explores the effectiveness of these tasks. It also examines the discrepancy in cognitive processes between different language competence levels in detail, shedding light upon current research on lecture comprehension assessment and offering insights into listening comprehension instruction.